Manual versus powered toothbrushes for oral health; an update - Yaacob, Munirah; Scott A, Deacon; Chris, Deery; Anne-Marie , Gleeny; Michael, Heanue; A Damien , Walmsley; Helen, Worthington; Peter G, Robinson (2011)

(untitled)
Background: Plaque removal is a cornerstone in the prevention and treatment of periodontal diseases. Powered toothbrushes have been devised to assist in plaque removal. An earlier Cochrane systematic review found that only powered toothbrushes with a rotation-oscillation action were more effective at removing plaque and reducing gingivitis. That review requires updating to include recent trials.